Neural network application in corporate bankruptcy prediction. - Xu, Xu Wei. (2009)
In today turbulent business climate, corporations have more exposure to bankruptcies than ever before. The recession in the early 1990s caused firms to experience severe cash flow problems that resulted in increased delinquency and failure rates.